Evaluation of Nutrition and Acceptability of Cookies Substituted with Millet Flour and Butterfly Pea Flower Extract (Clitoria ternatea) - Sotya Rawiningtyas; Hanafi; Nurhasanah; Tarich Majid Harsandi; Anisya Repika Sari; Dira Ekaputri; Isna Nur Hasanah; Muhammad Khaedar; Rudiansyah (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2024)
Cookies that are circulated in the community are generally made from wheat flour that is high in gluten. In addition, the high sugar content increases the risk of consumers to various metabolic diseases. Therefore, it is necessary to develop substituted cookie products and use natural ingredient extracts as natural additives that can improve the biological function of food so that cookies can be designed as functional foods in the future. This study aimed to determine the effect of substituting wheat flour with millet flour on cookies' acceptability, water, protein, and carbohydrate content. In this study, wheat flour raw materials were substituted using millet flour (50:50, 70:30, and 100:0). Butterfly pea flower extract was added to the cookie dough, and then proximate analysis and acceptance tests were carried out. The water content of substituted cookies was higher than the standard. The protein content of cookies substituted with millet flour is still by SNI standards. Meanwhile, the carbohydrate content per serving of substituted cookies is lower (51.78%) than standard cookies (70%). Meanwhile, the hedonic test showed that the substitution of millet flour (50:50) was still within the normal acceptance range according to SNI standards. Based on chemical content tests and acceptance tests, it is known that the substitution of millet flour with a composition of 50:50 still meets the biscuit criteria based on SNI.